Calculation algorithm of rational estimations of recurrence periodical fourth order fraction - Zatorsky, R.A.; Semenchuk, A.V. (Carpathian Mathematical Publications, 2014)
Recurrence fourth order fractions are studied. Connection with algebraic fourth order equations is established. Calculation algorithms of rational contractions of such fractions are built.